Synthesis of vicinal dideoxy-difluorinated galactoses. Issue 21 (16th May 2019) - Malassis, Julien; Vendeville, Jean-Baptiste; Nguyen, Qui-Hien; Boujon, Marie; Gaignard-Gaillard, Quentin; Light, Mark; Linclau, Bruno
Abstract : Three novel dideoxydifluorinated galactose derivatives are described. Abstract : Fluorinated carbohydrates have been employed as probes for fundamental studies of protein–carbohydrate interactions, but also in the development of mechanism-based enzyme inhibitors. There is a continuing demand for novel fluorinated carbohydrate probes. Whereas most examples so far involved monodeoxyfluorinated sugars, multiply deoxyfluorinated sugars have gained much interest. Here we report the synthesis and characterisation of novel vicinal dideoxy-difluorinatedd -galactoses with fluorination at the 3, 4-positions, and at the 2, 3-positions, the latter in both the pyranose and furanose forms. This includes a successful pyranose-into-furanose isomerisation protocol.